Pengembangan Wirausaha Budi Daya Dan Pemasaran Jahe Merah - Siti Nurjanah; Ferryal Abadi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
The Community Service (PKM) will be one of the bases for continuing to maintain or improve strategies that have been carried out in the community. Also, the PKM is part of one of the ways Kalbis Institute, in particular, the Management Study Program to develop entrepreneurial skills among farmers and management of community business actors. With this training, the benefits gained include: Sendang hamlet residents are motivated to increase their role in the family, especially members of the Tirta Asri Circle of Friends. The residents of Sendang hamlet can explore their interests and abilities for entrepreneurship in creative products, especially members of the Tirta Asri Circle of Friends. The residents of Sendang sub-village were able to cultivate red ginger well, especially members of the Tirta Asri. Keywords: entrepreneurship, red ginger